1990
DOI: 10.1002/gcc.2870010406
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular analysis of human male germ cell tumors: Chromosome 12 abnormalities and gene amplification

Abstract: We report karyotypic analysis of 24 male germ cell tumors (GCTs) with clonally abnormal karyotypes biopsied from testicular and extragonadal lesions from 20 patients belonging to the histologic categories seminoma, teratoma, embryonal carcinoma, choriocarcinoma, and endodermal sinus tumor. Chromosomes 1, 7, 9, 12, 17, 21, 22, and the X chromosome were nonrandomly gained in these tumors. Nonrandom structural changes affected most frequently chromosomes 1 and 12, the latter as i(12p) and/or del(12)(q13----q22). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(80 citation statements)
references
References 52 publications
(39 reference statements)
4
76
0
Order By: Relevance
“…Cytogenetically, i(l2p) can be detected in most TGCT [7,38,39], supported by molecular data [39, 4 0 ], The FISH approach [ll] is based on the use of a cen tromere specific probe for chromosome 12. This probe has been reported to detect a consistent size difference between the hybridizing region of a normal chromosome 12 and an i(12p), Because of a discrepancy in the literature regarding this phenomenon [18-20, 23, 41], as well as the occur rence of TGCT without i(12p) [1 3 , 20, 42], we studied the possibility of identifying 12p overrepresentation in gen eral, and of i(12p) in particular, on metaphase spreads and interphase nuclei with a double FISH approach.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetically, i(l2p) can be detected in most TGCT [7,38,39], supported by molecular data [39, 4 0 ], The FISH approach [ll] is based on the use of a cen tromere specific probe for chromosome 12. This probe has been reported to detect a consistent size difference between the hybridizing region of a normal chromosome 12 and an i(12p), Because of a discrepancy in the literature regarding this phenomenon [18-20, 23, 41], as well as the occur rence of TGCT without i(12p) [1 3 , 20, 42], we studied the possibility of identifying 12p overrepresentation in gen eral, and of i(12p) in particular, on metaphase spreads and interphase nuclei with a double FISH approach.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetically a specific chromosome marker has been found in more than 80% of testicular germ cell tumours: an isochromosome for the short arm of chromosome 12 [i(12p)] (Castedo et al, 1988;Samaniego et al, 1990). The i(12p) copy number has been reportd to have prognostic significance (Bosl et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] DNA quantification shows that mature ovarian teratomas are diploid, and cytogenetic study demonstrates that they almost always have a normal 46,XX karyotype, 10,11 whereas mature teratomas of the postpubertal testis are hyperdiploid to hypotriploid with complex cytogenetic abnormalities including invariable 12p amplification, often in the form of an isochromosome [i (12p)]. [12][13][14][15][16] Molecular genetic analysis has also shown that mature ovarian teratomas are usually homozygous for polymorphic markers, 17 indicating that they derive most often from a germ cell that has completed meiosis I but not meiosis II, a conclusion supported by cytogenetic analysis. 11 When heterozygosity does occur, it predictably is in loci that tend to be located distant from the centromere-that is, in genes most susceptible to crossing over at the metaphase plate of meiosis I.…”
Section: Mature Postpubertal Gonadal Teratomasmentioning
confidence: 99%